Validation of EORTC and CALGB prognostic models in surgical patients submitted to diagnostic, palliative or curative surgery for malignant pleural mesothelioma - Sandri, Alberto; Guerrera, Francesco; Roffinella, Matteo; Olivetti, Stefania; Costardi, Lorena; Oliaro, Alberto; Filosso, Pier Luigi; Lausi, Paolo Olivo; Ruffini, Enrico (Journal of Thoracic Disease, 2016)
Background: To assess the trend of our surgical patients affected by malignant pleural mesothelioma (MPM) and submitted to diagnostic/palliative or curative surgical procedures and to validate the European Organisation for Research and Treatment of Cancer (EORTC) prognostic score in our patient population. Methods: This is a cohort study of patients submitted to surgery for MPM from January 2007 to December 2013. Primary outcome was overall survival (OS). Univariate and multivariate-adjusted comparisons by EORTC prognostic score for OS were accomplished using Cox method. Adjusted models included the following clinical variables: kind of procedure, smoking habit, asbestos exposure, Charlson’s Comorbidity Index (CCI), clinical tumor stage, adjuvant chemotherapy, dyspnoea, chest pain and haematological variables according to the score features. Nomenclature of the surgical procedures matches the International Association for the Study Lung Cancer (IASLC)/International Mesothelioma Interest Group (iMIG). Results: One-hundred sixty-six consecutive cases were collected: the median age at surgery was 73 years and 123 patients (75%) had a history of asbestos exposure. Ninty patients (54%) were submitted to a palliative/diagnostic thoracoscopy, 30 to pleurectomy/decortication (P/D), and 6 to extra-pleural pneumonectomy (EPP). Clinical TNM stages were as follows: 99 (60%) stage I–II, 34 (20%) stage III and 33 (20%) stage IV. The median follow-up (FU) was 19 months [interquartile range (IQR), 9–31 months] and the FU-completeness was 98%. By the end of the study 130 patients died (78%). One- and 3-year OS was 60% and 36%, respectively. Patients submitted to EPP and P/D showed a better survival (P=0.013). Multivariable model showed an independent prognostic value of EORTC score (HR =2.86, P